Acceptability of virtual therapy for postpartum women during COVID-19: A national mixed methods study - Gonzalez, Carmen; Ramirez, Magaly; Mata-Greve, Felicia; Diaz, Autumn; Duran, Miriana C.; Johnson, Morgan; Grote, Nancy; Areán, Patricia A. (Frontiers in Psychiatry, 2022)
Background: Postpartum depression (PPD) affects one in eight women (CDC, 2020) with rates increasing due to the COVID-19 pandemic. Given the unique circumstances of COVID-19, virtual therapy might be a unique way to overcome barriers to mental health services. The study sought to explore the acceptability of virtual therapy among women in the postpartum period. Methods: Using an online recruitment mixed methods approach, we collected data from a U.S. national cross-sectional sample of women (N = 479) who gave birth in the last 12 months. Findings: Results show that 66% endorsed items consistent with possible depression during the COVID-19 pandemic. Only 27% accessed therapy services during the postpartum period. While 88% were open to engaging in virtual therapy services, 12% identified several major concerns with virtual therapy, namely: 1) preference for in-person therapy 2) no perceived need for therapy 3) uncomfortable with virtual therapy, and 4) lack of privacy. Of note, 36% more Latinas reported dissatisfaction with quality of care received during virtual therapy. Despite a major shift to virtual care with COVID-19, future work is needed to make virtual mental health services more approachable and culturally sensitive for women with PPD.